Correlation between Serum Ferritin, Serum Cystatin C, and Renal Function in Children with Î² Thalassemia Major (Majalah Kedokteran Bandung, 2019)
Renal dysfunction caused by iron overload is characterized by an increase in ferritin and cystatin C levels. The objective of this study was to determine the correlation between ferritin, cystatin C, and renal function in children with Î² thalassemia major. A cross-sectional observational analytic study was conducted in September 2018 on 34 children with Î² thalassemia major in Dr. Hasan Sadikin General Hospital. Ferritin and cystatin C levels were documented and the estimated glomerular filtration rate (eGFR) was calculated using the Schwartz formula. Statistical tests were performed using Rank Spearman and Point Biserial with p value of
Keywords: cystatin C; ferritin; renal function; Î² talasemia major children